The Effect of Learning Based on Errors Analysis on the ability of proportional reasoning - Amal Abdallah Khasawneh; Ali Ahmad Al-Barakat; Soliman Abedallteef Almahmoud (International Journal of Engineering Education, 2022)
The present study investigated the effect of learning based on analyzing mathematical errors on proportional reasoning ability. To achieve the purpose of the study, a proportion unit for the seventh grade students in Jordan was designed according to the learning based on error analysis. A sample of (45) seventh grade students participated in the study, and were randomly assigned into two groups; experimental and control. Data were collected through two instruments; a proportional reasoning test and an interview, after ensuring their reliability and validity. The results of the study revealed that learning based on the analysis of mathematical errors improved significantly proportional reasoning among the experimental group, and contributed in providing students with positive experiences in learning mathematics. In light of these results,  a set of recommendations for educational researchers, mathematics curriculum designers, and mathematics teachers were presented.